Anthropology of religion: the basics - James Bielo S (New York: Routledge, 2015)
"Anthropology of Religion: The Basics is an accessible and engaging introductory text organized around key issues that all anthropologists of religion face. This book uses a wide range of historical and ethnographic examples to address not only what is studied by anthropologists of religion, but how such studies are approached. It addresses questions such as:How do human agents interact with gods and spirits?What is the nature of doing religious ethnography? Can the immaterial be embodied in the body, language and material objects?What is the role of ritual, time, and place in religion?Why is charisma important for religious movements? How do global processes interact with religions?With international case studies from a range of religious traditions, suggestions for further reading, and inventive reflection boxes, Anthropology of Religion: The Basics is an essential read for students approaching the subject for the first time"--
"Anthropology of Religion: The Basics is an accessible and engaging introduction to the anthropology of religion. Organized around a series of research problems that all anthropologists of religion will inevitable face, it uses a wide range of historical and ethnographic examples to address not only what is studied by anthropologists of religion, but how such studies are approached. It addresses key questions such as: How do human agents interact with gods and demons? Why is charisma important for religious movements? Do global processes shape religion? Can the immaterial be embodied in the body, language and material objects? What is the role of ritual in religion? With international case studies from a range of religious traditions, suggestions for further reading and a glossary of key vocabulary, Anthropology of Religion: The Basics is an essential read for students approaching the study of the anthropology of religion for the first time"--
Keywords: Anthropology; Social Sciences